ECOLOGICAL NICHE BASED ON FISH FOOD COMPETITION AND FEEDING HABIT PATTERNS IN THE JATIBARANG RESERVOIR - Churun Ain; Sutrisno Anggoro; Dian Wijayanto; Siti Rudiyanti; Afifatul Isroliyah (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2021)
The purpose of this study was to determine ecological niche, the types of fish caught using gillnet and fishhook, the abundance of plankton, feeding habits and food competition in Jatibarang reservoir. The research was conducted from July until October, 2020. Tilapia (Oreachromis niloticus), Milkfish (Chanos chanos), Grass Carp (Ctenopharyngodon idella), Java Barb (Barbonymus gonionotus), and Red Devil (Amphilophus amarillo) were several types of fish found in the Jatibarang Reservoir. The total abundance of plankton was 4220 ind /, with L.Chlorophyceae dominating with a value 1780 ind / L and Zooplankton with the lowest abundance value of 20 ind / L. The result of the dominant Index of Preponderence (IP) showed Chlorophyceae class as the staple food of Tilapia, Grass Carp and Java Barb with values of 49.86%, 45.16% and 52.34% respectively. Milk fish and Red Devil had no main food (IP < 40%). The others class of plankton (Bacillariophyceae, Coscinodiscophyceae, Dinophyceae, Euglenoidea Cyanopyceae, Fragilariophyceae, and Zygnematophyceae) appeared as complementary foods (IP value 4-40%) and as additional food (IP value lesser than 4%). Milkfish was also found to have the highest ecological niche value of 4.577 and the Red Devil with the lowest value. The result of the niche overlap indicated the strongest good competition occurred between Tilapia and Gras Carp with a yield value of 1, and the lowest overlap value was found between Milkfish and Red Devil.